PARENTAL KNOWLEDGE AND BEHAVIOUR ABOUT DENTAL AND ORAL HEALTH CARE WITH EARLY CHILDHOOD CARIES OF 3-5 YEARS - Anie Kristiani; Tita Kartika Dewi; Hesti Sugesti (JDHT Journal of Dental Hygiene and Therapy, 2023)
Early Childhood Caries (ECC) is caries with a unique pattern of lesions in infants, toddlers and preschoolers caused by prolonged administration of formula milk or other sweet liquids. knowledge and attitudes of parents play an important role in underlying the formation of behavior that supports or does not support the maintenance of children's dental health. Purpose: this study aims to analyze the relationship between parental knowledge and behavior regarding dental and oral health maintenance and ECC in children aged 3-5 years at the Occupational Health Regional General Hospital, West Java Province. Method: this research is an analytic descriptive study with a cross sectional design. Data was taken by accidental sampling technique on 52 children aged 3-5 years. The procedure for filling out knowledge and behavior questionnaires by parents and clinical examination of the child's oral cavity using def-s was then classified based on the severity of ECC. Results: Parents' knowledge about dental and oral health maintenance was 36.5% good criteria, 32.7% sufficient criteria and 30.8% poor criteria. Parental behavior with good criteria 48.1%, sufficient criteria 44.2% and 7.7% less criteria. There were 28.9% of children with mild-moderate ECC, 36.5% moderate-severe and 34.6% severe. The results of the Chi Square test show a relationship between parental knowledge and ECC p value = 0.000 and parental behavior has a relationship with ECC p value = 0.448. Conclusion: there is a significant relationship between parents' knowledge about maintaining oral health and ECC in children aged 3-5 years, while the behavior of parents has no relationship with ECC in children aged 3-5 years.